CHRISTIAN DIMENSION OF GLOBALIZATION – SELECTED PROBLEMS - KĄDZIOŁKA, Władysław (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2022)
When we talk about globalization, we mean primarily the economic process leading to the formation of the «free world market», covering all areas of human activity: politics, law, culture, labor, information, etc. With television, the Internet and modern means of transport followed by a sharp increase in the exchange commercial and cultural – the world becomes small. It is a process that will lead to a new balance of power and the new geopolitical balance in the world in the twenty-first century. It should be emphasized that the Church made the first «globalization» as evangelism had and will have in the future worldwide. This means that the universal Church is the first «global» institution. It is also important to draw attention to the teaching of the Popes, who regularly return in their speeches, encyclicals and documents to the issue of globalization not only in the Christian, but also social, cultural, economic or political. The author of this article aims to trace the Christian dimension of globalization. An analysis of the extensive literature on globalization shows how topical this topic is. However, it becomes a problem to find publications dealing with Christian globalism, because this area has not yet been thoroughly explored and there is relatively little material on the subject. Globalization is a complex and multidimensional phenomenon. The correct approach to it can therefore only be the application of the «realistic method», which allows to capture globalization in all its dimensions. In this way, the author describes the anthropological and ethical dimensions, often overlooked, yet necessary to understand the deepest, also theological, meaning of this global process. The different dimensions of globalization should be united and imbued with the spirit of integral humanism. Catholic Social Teaching, re-read and updated in the light of «new things», can help in this. John Paul II, in his Message for the 2003 World Day of Peace, said that the time had come to «collaborate in creating a new organization of the whole human family», an organization that would be able to meet the new demands of a globalized world. This does not mean striving to create a «global superstate», but supporting processes already underway that enable democratic participation and foster accountability and integrity in the political arena.